2012
DOI: 10.1371/journal.pgen.1002634
|View full text |Cite
|
Sign up to set email alerts
|

Polyglutamine Toxicity Is Controlled by Prion Composition and Gene Dosage in Yeast

Abstract: Polyglutamine expansion causes diseases in humans and other mammals. One example is Huntington's disease. Fragments of human huntingtin protein having an expanded polyglutamine stretch form aggregates and cause cytotoxicity in yeast cells bearing endogenous QN-rich proteins in the aggregated (prion) form. Attachment of the proline(P)-rich region targets polyglutamines to the large perinuclear deposit (aggresome). Aggresome formation ameliorates polyglutamine cytotoxicity in cells containing only the prion form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 80 publications
1
56
0
Order By: Relevance
“…The neurodegeneration caused by various polyQ expansion proteins is highly cell specific, despite the fact that these proteins are broadly expressed throughout the body. Thus, toxicity in any particular cell type must be influenced by the sequences flanking the polyQ segments and the unique proteomes of the susceptible cell types (5,18,19). We do not, therefore, suggest that our yeast suppressors are directly relevant to human disease.…”
Section: Resultsmentioning
confidence: 92%
“…The neurodegeneration caused by various polyQ expansion proteins is highly cell specific, despite the fact that these proteins are broadly expressed throughout the body. Thus, toxicity in any particular cell type must be influenced by the sequences flanking the polyQ segments and the unique proteomes of the susceptible cell types (5,18,19). We do not, therefore, suggest that our yeast suppressors are directly relevant to human disease.…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have shown that overproduction of Sup35NM and expression of expanded polyglutamine in yeast can cause cytotoxicity through sequestration of the termination factors Sup35 and Sup45. 57,70 Thus, it is possible that the absence of RAC function enhances sequestration of essential factors by Sup35NM and polyglutamine. Regardless of the mechanism, the potential for cytotoxicity may be partially abrogated by the reduction in protein synthesis that occurs during the kinds of stresses that may trigger RAC dissociation from ribosomes.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the association of molecular chaperones of the Hsp70 and Hsp90 systems with the polyQ aggregates was enhanced, and their ability to sequester nuclear proteins was strongly reduced. Protein sequestration into aggregates may lead to an impairment of multiple key cellular pathways and is considered an important mechanism of aggregate toxicity (7,9,10,32,50,(53)(54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%